Annals of Academic Life: An Exemplary Tale - Kampf, Louis (Radical Teacher, 2014)
The narrator of the following vignette is not to be mistaken for the author. Though the tale appears to be autobiographical, it must be a fiction. Academic institutions, as we know, are the repositories of rationality. Professors have been bequeathed the patrimony of the Enlightenment. Such evidence indicates that the events described below could not possibly have happened.